AN ANALYSIS OF CULTURAL CONTENT IN THE TEXTBOOK â€œPATHWAY TO ENGLISHâ€ FOR SECOND GRADE IN SENIOR HIGH SCHOOL - Ine Nurjanah; Amroh Umaemah (IAIN Syekh Nurjati Cirebon, 2019)
Abstract: Some teachers English only focus on Â studentsâ€™ four skills and do not introduce about Â the culture, especially in learning English. Then, the student donâ€™t know about the culture.Â Cultural content is not taught directly. It can introduce through the textbook. So this way the important thing to the teacher should choose the appropriate textbook for teaching and learning language without leaving the culture that represented in the textbook. This research investigates the representation of culture-related contents in English textbooks entitled â€œPathway to Englishâ€ that published by Erlangga for second grade in senior high school in Indonesia. A content analysis of these textbooks was conducted, using two aspects of culture, â€˜cultural categoriesâ€™ and the â€˜cultural dimensionsâ€™ as the evaluation framework. In this research analayzed 14 chapters, 53 reading passages that was analyzed. Based on the result of the data that was analyszed. The are two aspect that present in this research. The first aspect is the cultural categories of Cortazzi and Jin (1999), and that has most huge amount of the porpostion is target culture. The country that use English as official language. Next, the other cultural categories that has small partÂ is local culture and the last which has the the smallest part is international culture. The second aspect is five dimentions of Moranâ€™s theory (2001). The most that has huge amount of porpotion in five dimentions is product the second part is person and community. Practice and perspective are the small part that represent in the textbook.Â